The Effect of Ethanol Addition on Vehicle Fuel Consumption in Economic Terms - A Review - Muhsin Muhsin; Suharno Suharno (Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2021)
The technological development of the automotive sector is increasing, every year there is an increase in the production of motor vehicles in Indonesia. The increase in motorized vehicles will certainly have an impact on the use of fuel oil which is also increasing. Though fuel oil is a non-renewable fossil fuel, so that continuous use can lead to scarcity of fossil fuels someday. In addition to causing scarcity of fossil fuels, the increasing number of vehicles will also cause the surrounding environment to be increasingly polluted by the exhaust emissions from the combustion process of the motorized vehicles. Various alternatives are used as a mixture of fuels to reduce fuel consumption and vehicle exhaust emissions, such as ethanol, hydrogen, butanol, biodiesel, methanol etc. The purpose of this literacy study was to determine the effect of using ethanol on fuel consumption and its economic value. Based on the results of a study of literacy is known that the addition of ethanol does reduce the level of fuel consumption, However, if viewed from an economic perspective, the addition of ethanol has actually caused the purchase price of fuel to increase, this will certainly hinder the growth of the desire to use ethanol as an alternative source of fuel substitute by the people of Indonesia.